A Simulation Study on the Thermal Shock Behavior of Tungsten Mock-Up under Steady-State Heat Loads. Issue 12 (December 2016) - Wang, Yanxin; Wang, Shuming; Ye, Qing; Yan, Qingzhi; Ge, Changchun
Abstract : In a fusion reactor, due to high heat flux (HHF) loads, the plasma facing components (PFCs) will suffer severe thermal shock. In this paper, the temperature distribution and thermal-stress field of tungsten armor under HHF loads were investigated by the method of finite element modeling and simulating. The orthogonal experiment and range analysis were employed to compare the influence degree of four representative factors: steady-state heat flux; thickness of tungsten armor; inner diameter of cooling tube and the coefficient of convection heat transfer (CCHF) of cooling water, on thermal shock behavior tungsten mock-ups, and then get an optimization model to conduct the transient heat flux experiment. The final simulation results indicated that the steady-state heat flux and the thickness of W armor are the main influential factors for the maximum temperature of mock-ups. Furthermore, the influence of transient thermal shock all mainly concentrates on the shallow surface layer of tungsten (about 500 µm) under different transient heat flux (duration 0.5 ms). The results are useful for the structural design and the optimization of tungsten based plasma facing materials for the demonstration reactor (DEMO) or other future reactors.